SOME KINDS OF DISEASES AND PESTS OF GRAPES AND METHODS OF CONTROL THEM IN THE ARARAT VALLEY - BABAYAN, ARMAN HRANTOVICH (International Journal of Psychosocial Rehabilitation, 2020)
n this article, we will consider two main problems of vineyards - these are some diseases and pests of grapes that prevail in the Ararat valley. Let’s list them: twospotted spider mite (Tetranychus urticae), European grape moth (Polychrosis botrana), anthracnose of grapes, mildew and gray rot (botrytis cinerea).